Gc-Ms Analysis Of Phytochemical Constituents In Leaf Extracts Of Neolamarckia Cadamba (Rubiaceae) From Malaysia - Mohamed, Zaky Zayed; Fasihuddin Badruddin, Ahmad; Wei-Seng, Ho; Shek-Ling, Pang (Innovare Academic Sciences, 2014)
Neolamarckia cadamba is one of the medicinal plants used in the treatment of various diseases traditionally. This study was conducted to identify the phytochemical constituents of N. cadamba leaf extracts using gas chromatography mass spectrometry (GC-MS). Solvents with increasing polarities viz. hexane, petroleum ether, chloroform, ethyl acetate and methanol were used in this study. The solvent extracts were analyzed using GC-MS and the mass spectra of the compounds found in the respective extract were matched with the National Institute of Standards and Technology (NIST) library. A total of 26 compounds were identified and the major chemical constituents were n-hexadecanoic acid (44.88%), hexadecanoic acid ethyl ester (17.96%) and octadecanoic acid ethyl ester (11.71%). Some of the identified compounds have been reported to possess various biological activities such as antioxidant, antimicrobial, anesthetic, antiseptic, antidiabetic, hypocholesterolemic and etc. The results thus concluded that N. cadamba leaves possess various potent bioactive compounds and is recommended as a plant of phytopharmaceutical importance.